Deficiency in insulin‐like growth factors signalling in mouse Leydig cells increase conversion of testosterone to estradiol because of feminization. (2nd October 2020) - Radovic Pletikosic, Sava M.; Starovlah, Isidora M.; Miljkovic, Dejan; Bajic, Dragana M.; Capo, Ivan; Nef, Serge; Kostic, Tatjana S.; Andric, Silvana A.
Abstract: Aim: A growing body of evidence pointed correlation between insulin‐resistance, testosterone level and infertility, but there is scarce information about mechanisms. The aim of this study was to identify the possible mechanism linking the insulin‐resistance with testosterone‐producing‐Leydig‐cells functionality. Methods: We applied in vivo and in vitro approaches. The in vivo model of functional genomics is represented by INSR/IGF1R‐deficient‐testosterone‐producing Leydig cells obtained from the prepubertal (P21) and adult (P80) male mice with insulin + IGF1‐receptors deletion in steroidogenic cells ( Insr/Igf1r ‐DKO). The in vitro model of INSR/IGF1R‐deficient‐cell was mimicked by blockade of insulin/IGF1‐receptors on the primary culture of P21 and P80 Leydig cells. Results: Leydig‐cell‐specific‐insulin‐resistance induce the development of estrogenic characteristics of progenitor Leydig cells in prepubertal mice and mature Leydig cells in adult mice, followed with a dramatic reduction of androgen phenotype. Level of androgens in serum, testes and Leydig cells decrease as a consequence of the dramatic reduction of steroidogenic capacity and activity as well as all functional markers of Leydig cell. Oppositely, the markers for female‐steroidogenic‐cell differentiation and function increase. The physiological significances are the higher level of testosterone‐to‐estradiol‐conversion in double‐knock‐out‐mice of both ages and few spermatozoa in adults. Intriguingly, the transcription of pro‐male sexual differentiation markers  Sry/Sox9  increased in P21‐Leydig‐cells, questioning the current view about the antagonistic genetic programs underlying gonadal sex determination. Conclusion: The results provide new molecular mechanisms leading to the development of the female phenotype in Leydig cells from  Insr / Igf1r ‐DKO mice and could help to better understand the correlation between insulin resistance, testosterone and male (in)fertility.